Extended planning poker: A proposed model - Sudarmaningtyas, Pantjawati; Rozlina, Mohamed (IEEE, 2020)
Agile is the leading type of software development methodology and have a higher chance of success than non-agile projects. Collaborative and cooperative are characteristic of the Agile software development method. It is demonstrated by involving users actively, empower the team to make decisions, capture requirements in lightweight and visual, focus on frequent delivery of products through developing small, incremental release, and iterate. This characteristic is causing effort estimation remains the main challenge in agile software development. Planning poker is an effort estimation technique that applied extensively with the ability to empower all team developers to decide, especially in estimate effort. Still, the result is very subjective and takes a long time. This research proposes a new model to improve actual planning poker performance. A proposed model modify two parts of the planning poker is the estimation process and consensus process. Three variables added to the estimation process as well as implementing weight and score for its variables. The consensus process proposed done automatically based on five attributes that are related to the estimator.